Respuesta :

Answer:

[tex]9(b + 5) - 4b = \\ 9b + 45 - 4b = \\ 5b + 45 = b + 9[/tex]

Hope it helps you<3

[tex] \looparrowright \sf9(b + 5) - 4b[/tex]

[tex] \\ \\ [/tex]

[tex] \looparrowright \sf9b + 45 = - 4b[/tex]

[tex] \\ \\ [/tex]

[tex] \looparrowright \sf9b + 4b + 45 = 0[/tex]

[tex] \\ \\ [/tex]

[tex] \looparrowright \sf5b + 45 = 0[/tex]

[tex] \\ \\ [/tex]

[tex] \looparrowright \sf5b = - 45[/tex]

[tex] \\ \\ [/tex]

[tex] \looparrowright \sf \: b = - 45 \div 5[/tex]

[tex] \\ \\ [/tex]

[tex] \looparrowright \sf \: b = -9[/tex]